A Gain-of-Function Mutant of IAA15 Inhibits Lateral Root Development by Transcriptional Repression of LBD Genes in Arabidopsis - Kim, Sun Ho; Bahk, Sunghwa; An, Jonguk; Hussain, Shah; Nguyen, Nhan Thi; Do, Huy Loc; Kim, Jae-Yean; Hong, Jong Chan; Chung, Woo Sik (Frontiers in Plant Science, 2020)
Lateral root development is known to be regulated by Aux/IAA-ARF modules in Arabidopsis thaliana. As components, several Aux/IAAs have participated in these Aux/IAA-ARF modules. In this study, to identify the biological function of IAA15 in plant developments, transgenic plant overexpressing the gain-of-function mutant of IAA15 (IAA15P75S OX) under the control of dexamethasone (DEX) inducible promoter, in which IAA15 protein was mutated by changing Pro-75 residue to Ser at the degron motif in conserved domain II, was constructed. As a result, we found that IAA15P75S OX plants show a decreased number of lateral roots. Coincidently, IAA15 promoter-GUS reporter analysis revealed that IAA15 transcripts were highly detected in all stages of developing lateral root tissues. It was also verified that the IAA15P75S protein is strongly stabilized against proteasome-mediated protein degradation by inhibiting its poly-ubiquitination, resulting in the transcriptional repression of auxin-responsive genes. In particular, transcript levels of LBD16 and LBD29, which are positive regulators of lateral root formation, dramatically repressed in IAA15P75S OX plants. Furthermore, it was elucidated that IAA15 interacts with ARF7 and ARF19 and binds to the promoters of LBD16 and LBD29, strongly suggesting that IAA15 represses lateral root formation through the transcriptional suppression of LBD16 and LBD29 by inhibiting ARF7 and ARF19 activity. Taken together, this study suggests that IAA15 also plays a key negative role in lateral root formation as a component of Aux/IAA-ARF modules.